Suppression of PI3K/Akt/mTOR pathway in chrysoeriol-induced apoptosis of rat C6 glioma cells - Suppanut Wongkularb (2022)
Chrysoeriol, a dietary methoxyflavonoid which is found in tropical medicinal plants, has been shown to have antioxidant, anti-inflammatory, and antineoplastic properties. The present study aimed to investigate the effects of chrysoeriol and its related mechanisms in rat C6 glioma cells. Cell viability in rat C6 glioma cells were measured by MTT assay. The protein expression levels of cleaved caspase-3, caspase-3, pro-apoptotic (Bax), anti-apoptotic protein (Bcl-2), and Annexin V were detected by Western blot analysis and immunocytochemical staining. Results showed that chrysoeriol significantly decreased cell viability and induced apoptosis in rat C6 glioma cells. Chrysoeriol significantly increased the levels of Bax/Bcl-2 ratio and cleaved caspase-3/caspase-3 ratio. Moreover, treatment with chrysoeriol significantly reduced the phosphorylation of PI3K, Akt, and mTOR expression in ratios. These results suggest that chrysoeriol promote apoptosis in rat C6 glioma cells via suppression of the PI3K/Akt/mTOR signaling pathway, thereby demonstrating the potential antineoplastic effects of chrysoeriol on glioma cells.